Binding earth and heaven patriarchal blessings in the prophetic development of early Mormonism - Shepherd, Gary, 1943-; Shepherd, Gordon, 1943- (University Park, Pennsylvania : The Pennsylvania State University Press, 2012)
"Focuses on Mormonism as a case study of how unpopular new religions may survive and even flourish in spite of unrelenting opposition. Examines early patriarchal blessings bestowed upon early converts to Mormonism from 1834-1845, and their function as a commitment mechanism for converts"--Provided by publisher.
The commitment and doctrinal functions of early Mormon patriarchal blessings -- Unity and conflict in early Mormon history -- The office and calling of the Church patriarch -- The problems and promise of patriarchal blessings as historical artifacts -- Patriarchal blessing themes, 1834/1845 -- Gender differences in early patriarchal blessings -- Latter-day Saint patriarchal blessings yesterday and today -- Appendix A: examples of oracular versus inspirational modes of prophetic rhetoric -- Appendix B: blessings randomly sampled from Marquardt's Early patriarchal blessings -- Appendix C: thematic word index for patriarchal blessings.
Includes bibliographical references (p. [153]-162) and index.
Description based on print version record.
Keywords: Church of Jesus Christ of Latter-day Saints -- History -- 19th century; Patriarchal blessings (Mormon Church); Mormon Church -- History -- 19th century; RELIGION / Christian Rituals & Practice / Worship & Liturgy; RELIGION / Institutions & Organizations; Electronic books